Menilik Peraturan Dan Pelanggaran Pemilu: Edukasi dan Pendampingan Warga Desa Peguyangan Kangin - I Gede Egga Putra Setiawan; Dewa Ayu Putu Adhiya Garini Putri (Universitas Serang Raya, 2024)
Elections are a common thing among Indonesian people and are also one of the things that is mandatory to form a sovereign state. Holding fair elections is very important, because elections themselves are the main means for democracy, and at the same time the realization of the will of the people. The large number of cases of election violations and the disproportionate number of findings and reports obtained indicate a lack of effective law enforcement. The aim of holding this service activity is to understand the community about existing regulations so that if there is a violation of election regulations, the community can voice their disagreement. Based on the participants' accounts, they were satisfied with every explanation given by the presenters and they understood that they had the right to receive as much information as possible about the offers they wanted to convey and election participants also expressed their programs and ideas. Violations that often occur are usually administrative in nature and take the form of election criminal violations, therefore the KPU should frequently hold outreach regarding problems, namely looking at election regulations and violations: education and assistance to Peguyangan Kangin village residents. The method used is to provide political education to the community so that the final result is that the community can differentiate between existing regulations whether during the campaign a political party has violated existing regulations or not.